Cardiac Tamponade - Zapata Uribe, Pedro; Abreu, Phillipe; Garzesi, André Monti [UNESP]; Garcia, Leonardo Rufino [UNESP]; Felicio, Marcello Laneza [UNESP]; Brenner Affonso da Costa, Ana Cláudia (Springer Nature, 2025)
In a simple way, the pericardium can be described as the membrane that externally covers the heart. It can be divided into visceral and parietal. The visceral pericardium is composed of cells juxtaposed to the epicardium, and the parietal pericardium is fibrous, composed of collagen, and has a thickness of about 2 mm. Between these layers remains the pericardial cavity, which contains about 50 mL of fluid.